2013
DOI: 10.1111/wre.12058
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of mowing and bud destruction on Centaurea solstitialis growth, flowering, root dynamics and soil moisture

Abstract: Both treatments reduced mean capitulum diameter. This resulted in reductions of 76% and 21% in estimated seed number for mowed and bud damaged plants respectively. Root abundance decreased and root life-span was reduced by both treatments. Soil moisture depletion was greatest from mid-May to mid-July (from 21% to 9%) and occurred after maximum root abundance. Mowing resulted in a delay in soil moisture depletion compared with the bud damaged plants or the untreated controls. Bud/capitula damage did not affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…These late capitula contributed only 6% of the total seasonal production of seed. Spencer et al [ 32 ] showed that early bud loss on C. solstitialis reduced capitulum size, which resulted in a reduction of 21% in expected seed output per plant. At the Napa site in 1995, the mean capitula diameter for plants with E. villosus was 7% smaller than the mean capitula diameter for plants without the weevil, suggesting that adult feeding damage of immature buds may result in smaller capitula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These late capitula contributed only 6% of the total seasonal production of seed. Spencer et al [ 32 ] showed that early bud loss on C. solstitialis reduced capitulum size, which resulted in a reduction of 21% in expected seed output per plant. At the Napa site in 1995, the mean capitula diameter for plants with E. villosus was 7% smaller than the mean capitula diameter for plants without the weevil, suggesting that adult feeding damage of immature buds may result in smaller capitula.…”
Section: Discussionmentioning
confidence: 99%
“…Adult weevils emerge in late spring and undergo a period of host feeding. Adults of both sexes feed on young flower buds (<3 mm in diameter) [ 30 , 31 , 32 ]. This early bud feeding can be severe and many plants can lose all initial flower buds.…”
Section: Methodsmentioning
confidence: 99%
“…However, an experimental field study failed to show population‐level impact of capitula insects on YST population density (Garren & Strauss, ). Mowing experiments reduced YST growth and reproduction more than herbivore capitula damage alone (Spencer et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of Peng [ 36 ], two categories of old and medium adult trees have grown for more than 15 years; that is, the occurrence of these individuals, prior to the implementation of the alternative seasonal grazing-mowing regime, is a result of interactions among year-round free grazing and abiotic factors (such as climate, soil and microgeomorphology)[ 48 ]. There are fewer juvenile trees in all 3 plots, therefore their spatial pattern have not been analysed in this study ( Table 1 ; Fig 8 and S5 Fig ), the individual age of the juvenile tree category is less than 15 years old, which coincides with the implementation period of the alternative seasonal grazing-mowing regime to a great extent; it can be deduced that the majority of one-year or multiyear seedlings that remained and grew from juveniles to adults[ 49 , 50 ] during the year-round free grazing procedure due to selective feeding of livestock, might be harvested by the nonselective mowing activity in autumn[ 51 54 ]. This deduction can better explain why numerous seedlings (germinated mostly in the current year) existed in aggregations in our August investigation.…”
Section: Discussionmentioning
confidence: 99%